2017
DOI: 10.3892/etm.2017.5140
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‑enhanced computerized tomography combined with a targeted nanoparticle contrast agent for screening for early‑phase non‑small cell lung cancer

Abstract: Abstract. Non-small cell lung cancer (NSCLC) is a major cause of morbidity and mortality, and patients with NSCLC are frequently diagnosed at an advanced stage. This is primarily due to a lack of advanced and sensitive protocols for the detection of early stage NSCLC. Therefore, methods for the accurate diagnosis of early stage NSCLC are urgently required to improve survival rates. The present study investigated the use of contrast-enhanced computerized tomography (CECT) combined with a targeted nanoparticle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Taken together, the data obtained in the present study indicates that GdCho-Len is a stable and safe nanoparticle contrast agent for diagnosing patients with lung cancer. Contrast agent may increase the sensitivity and accuracy of CT imaging for the diagnosis of early stage NSCLC (23). A novel nano-sized chistosan/Fe 3 O 4 -enclosed bispecific antibody had been identified as an efficient contrast agent in lung cancer diagnosis (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the data obtained in the present study indicates that GdCho-Len is a stable and safe nanoparticle contrast agent for diagnosing patients with lung cancer. Contrast agent may increase the sensitivity and accuracy of CT imaging for the diagnosis of early stage NSCLC (23). A novel nano-sized chistosan/Fe 3 O 4 -enclosed bispecific antibody had been identified as an efficient contrast agent in lung cancer diagnosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that developing multimodal contrast agent would enhance the diagnostic accuracy of PET/CT, as well as increase the diagnostic accuracy sensitivity in patients with lung cancer (23). A previous study reported that contrast-enhanced ultrasound with a novel nanoparticle contrast agent increases the diagnostic efficacy in patients with NSCLC (24).…”
Section: Role Of Gd 2 O 3 -Doped Carbon-11-choline-lenvatinib Nanoparmentioning
confidence: 99%
“…Moreover, the systemic delivery of the binary system by retro-orbital injections caused irreversible changes in the injection region that might have reduced the delivery efficiency, especially in the later steps. Better diagnostic tests that discover earlier stages of the lung cancer such as luc bioluminescence imaging [ 60 ], small-molecular fluorescent probes [ 61 ] or contrast-enhanced computerized tomography [ 62 ] for earlier DNA deliveries may lead to an improved or complete survival. Moreover, a combination of the binary system with different anti-cancer approaches may enhance the longevity of the treated cancer mice.…”
Section: Discussionmentioning
confidence: 99%
“…The development of imaging technology, such as computed tomography (CT), has increased the identification and surgical treatment of small‐sized non–small cell lung cancer (NSCLC) in recent years. 1 Previous studies have reported that small‐sized NSCLC with ground‐glass opacity (GGO) is non‐invasive with little vessel invasion or lymph node metastasis and has an improved prognosis compared to tumors without GGO 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ; this is because the GGO component is usually pathologically equivalent to a lepidic growth component (LGC). 2 , 12 , 13 , 14 , 15 Therefore, some researchers have suggested that the stage of NSCLC can be determined by the GGO component.…”
Section: Introductionmentioning
confidence: 99%